When the scan tells a different story - Matthew S. Berniard; Monika Krzak; Richard Slama; Charles Dalton Hardesty; Carlo Zamora; Christina Cartwright (JEM Reports, 2025)
Background: Point-of-care ultrasound (POCUS) has become a standard in emergency care for its rapid, accurate bedside diagnostics and procedural guidance. Our institution developed a tailored, comprehensive POCUS course aligned with American Board of Emergency Medicine guidelines. Unlike many physician-only programs, our course also trains Advanced Practice Providers (APPs) alongside their supervising physicians. Two weeks after completing the course, an APP applied this training in a rare case, directly contributing to a life-saving intervention. While not a substitute for residency-based ultrasound training, this experience highlights the powerful impact of structured ultrasound education for all emergency providers. Case report: A 33-year-old male presented to the emergency department (ED) with progressively worsening, atraumatic, right knee and calf pain over a two-week period leading to difficulty ambulating. Initially evaluated by an APP in the low-acuity area, a supervising physician was consulted to proctor and perform a proximal lower extremity POCUS for suspected deep vein thrombosis (DVT). While no DVT was identified, the scan revealed a 3.8 cm arterial structure consistent with a massive popliteal artery aneurysm. Computed Tomography Angiography confirmed the diagnosis and raised concern for rupture. The patient was taken emergently for bypass surgery. Investigation revealed the aneurysm was secondary to tertiary syphilis in the setting of undiagnosed human immunodeficiency virus (HIV). Why should an emergency physician be aware of this?: Emergency Medicine physicians should embrace the broad utility of ultrasound as a rapid, accurate, and cost-effective diagnostic tool that enhances patient care, especially in resource-limited settings. This case underscores ultrasound's role in the timely diagnosis and treatment of vascular emergencies, while highlighting the need for comprehensive ultrasound training programs inclusive of all provider types.